Pancreatic tumors - Centeno, Barbara Ann; Dhillon, Jasreman (Basel Karger, 2020)
The outstanding feature of this publication is that it illustrates in detail the broad range of pancreatic lesions most likely to be encountered on fine needle aspiration of the pancreas, incorporating ancillary testing and differential diagnoses. Detailed descriptions of the cytological features of nonneoplastic entities, ductal and nonductal primary neoplasms, nonneoplastic and neoplastic cystic lesions, and secondary tumors and mesenchymal lesions are included. A multidisciplinary authorship has created a well-rounded presentation of the clinical, imaging, and histopathological features of each lesion. A chapter on specimen processing provides guidance on cytological preparation of samples from solid and cystic lesions. This monograph is written for cytotechnologists, general pathologists, and cytopathologists who work with pancreatic fine needle aspiration in their practice. It is also a useful guide to pancreatic cytology for advanced endoscopists, surgeons, and oncologists who evaluate, manage, and treat patients with pancreatic masses.
Keywords: PÁNCREAS -- NEOPLASMAS; PÁNCREAS -- CITOLOGÍA